A Comparative Study On Biosynthesis Of Xanthan Gum Using Three Different Xanthomonas Strains Isolated From Diseased Plants - S.ANBUSELVI; M. SATHISH KUMAR; M.VIKRAM; PADMAJA (International Journal of Pharma and Bio Sciences, 2012)
Naturally occurring bacterium Xanthomonas strains like X.campestris,X. malvacearum and X.axonopodis were isolated from diseased plants and identified. They were used for xanthan gum production by fermentation with different carbon and nitrogen sources. The effect of pH and temperature were also determined during the production of xanthan gum. This extracted polymer was then purified with alcohol, dried and milled. The viscosity of the xanthan gum produced was found. The biomass and yield of xanthan gum were determined.